2016
DOI: 10.3847/1538-4357/833/1/65
|View full text |Cite
|
Sign up to set email alerts
|

BOOSTING LYα  AND He ii λ1640 LINE FLUXES FROM POPULATION III GALAXIES: STOCHASTIC IMF SAMPLING AND DEPARTURES FROM CASE-B

Abstract: We revisit calculations of nebular hydrogen Lyα and HeII λ1640 line strengths for population III galaxies, undergoing continuous and bursts of star formation. We focus on initial mass functions (IMFs) motivated by recent theoretical studies, which generally span a lower range of stellar masses than earlier works. We also account for case-B departures and the stochastic sampling of the IMF. In agreement with previous works, we find that departures from case-B can enhance the Lyα flux by a factor of a few, but w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 108 publications
0
23
0
Order By: Relevance
“…Under the assumption that N(Lyα) = N(MUV) (being Lyα and MUV referring to the same star complex), the resulting TIGM(Lyα) are 0.09, 0.11, and 0.16, respectively. These values double if the case-B is assumed, i.e., the predicted L(Lyα) is about a factor two fainter (Mas-Ribas et al 2016). With such values of TIGM(Lyα) the resulting EW0(Lyα) ranges between 4000-1500Å, for the three classes of Pop III stellar masses.…”
Section: Candidate Pop III Starsmentioning
confidence: 94%
“…Under the assumption that N(Lyα) = N(MUV) (being Lyα and MUV referring to the same star complex), the resulting TIGM(Lyα) are 0.09, 0.11, and 0.16, respectively. These values double if the case-B is assumed, i.e., the predicted L(Lyα) is about a factor two fainter (Mas-Ribas et al 2016). With such values of TIGM(Lyα) the resulting EW0(Lyα) ranges between 4000-1500Å, for the three classes of Pop III stellar masses.…”
Section: Candidate Pop III Starsmentioning
confidence: 94%
“…For our lower limit SFE of 0.1% in Halo A we get a total of ≈ 10 4 M in stars. Mas-Ribas, Dijkstra & Forero-Romero (2016) show that for a total stellar mass of 10 3 M , there is a factor of few difference in the LW flux for different stochastically sampled IMFs, but this is much reduced for ≈ 10 4 M in stars.…”
Section: Star Formation Efficienciesmentioning
confidence: 99%
“…We create a stellar population from a flat slope IMF within the mass range 9 -500 M , using the stellar SEDs and same methodology as in Mas-Ribas, Dijkstra & Forero-Romero (2016); we refer the reader to that work for a detailed description of the calculations. These authors used parameters from Schaerer (2002) and Marigo et al (2001), and assumed the stars to be metal-free and to reside on the main sequence.…”
Section: Flat Slope Imf From Pop III Stellar Spectramentioning
confidence: 99%
“…It has been shown that assuming different mostly changes the peak value of the EW 0 distribution but does not increase its width (e.g., Garel et al 2015), unless one adopts evolving or spatially varying IMFs within galaxies (e.g., Orsi et al 2012). Nevertheless, at fixed IMF, Forero-Romero & Dijkstra (2013) hinted that the stochastic sampling of the IMF can induce fluctuations in the predicted EW 0 values for a given star formation event, hence broadening the EW 0 distributions (see also Mas-Ribas et al 2016). Alternatively, bursty star formation may also help reconcile models and observations.…”
Section: Lyα Emission Powered By Star Formationmentioning
confidence: 99%